GEN Z'S INFORMATION BEHAVIOR IN THE ERA OF AI: A STUDY APPLYING WILSON'S THEORY (CASE STUDY IN JAVA ISLAND) - Aam Mariyamah; Majidah Majidah (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Information behavior refers to all activities related to human interaction with information. Generation Z (Gen Z), the generation born in the technological era, is no stranger to the use of artificial intelligence (AI) in their daily lives. This study aims to analyze Gen Z's information behavior in this AI era from the perspective of Wilson's Information Behavior Theory (1996). The variables examined include passive attention, passive search, active search, and ongoing search information behaviors. Data analysis was conducted descriptively and inferentially using Moderated Regression Analysis (MRA) with the help of SPSS 26.0 software The research instrument used an online questionnaire. The research respondents consisted of 260 Gen Zers spread across the island of Java. Respondents came from diverse demographic backgrounds, such as freelancers, students, and housewives. The results of the study show that demographic differences did not significantly affect AI usage patterns, as the majority of respondents (77.5%) chose AI personalization on social media as the most frequently used AI. Further findings show that the average values for information behavior are passive attention at 4.05, passive search at 3.91, active search at 4.04, and ongoing search at 3.97. This indicates that Gen Z in the AI era has a fairly balanced pattern of information behavior. They are not only passive in interacting with information that often comes by chance through social media algorithms, but also actively search for information when needed through search engines. Overall, this study shows that AI-based digital environment factors have a stronger influence than demographic factors in shaping Gen Z's information behavior. This also shows the relevance and expansion of the application of Wilson's Theory (1996) in the context of AI.